Backgrounds of violence in young people - KACEMI, Bouabdallah (Social Sciences Journal)
The problem of violence and youth are frequently in the public or private space of ,could not without days or weeks without to read or hear or see the multiple forms of violence in urban areas and through the media fluid. This makes us to raise several questions about this phenomenon and practices among young people to know what is behind her motives and mechanism which give rise to have the desire to exercise violence in urban areas.The revival of the city of Oran sample are similar to those practices that assume to us the seriousness of the situation if not every one of us according to his competence, in turn, to understand the real motives of the backgrounds and the reasons that make these young people a taste of social ills.